The Mutual Effect of Marital Quality and Parenting Stress on Child and Parent Depressive Symptoms in Families of Children with Oppositional Defiant Disorder - Lin, Xiuyun; Zhang, Yulin; Chi, Peilian; Ding, Wan; Heath, Melissa A.; Fang, Xiaoyi; Xu, Shousen (Frontiers in Psychology, 2017)
The purpose of the current study was to examine the mutual relationships between dyadic level (i.e., marital quality and parenting stress) and individual level factors (i.e., children and parental depressive symptoms) in families of children with Oppositional Defiant Disorder (ODD). Specifically, we explored whether marital interaction (marital quality) was associated with symptoms of child depression through parent-child interaction (parenting stress) and parent depressive symptoms. We also explored whether parent-child interaction was associated with symptoms of parent depression through marital interaction and child depressive symptoms. This study was conducted with 256 parent-child dyads, consisting of children with ODD and one of each child's parents. Participants were recruited from 14 primary schools located in northern, eastern, and southwestern China. Results revealed that marital quality predicted symptoms of child depression through the parenting stress, but not parent depressive symptoms; and parenting stress predicted symptoms of parent depression through marital quality, but not through child depressive symptoms. Also, parenting stress significantly and directly predicted parent depressive symptoms. We concluded in families of children with ODD, the association of marital interaction and parent-child interaction on both symptoms of parent and child depression highlighted the mutual effects of the couple subsystem and the parent-child subsystem. Furthermore, in regard to parental and child depressive symptoms, implications for intervention are provided.